Neoliberal Agendas in English Language Education in Urban Latin America : The Case of Medellín, Colombia (2024)
ABSTRACT: In this article we discuss the findings of a diagnostic study of (foreign and native) language use in the department of Antioquia, in the Northwest region of Colombia; we specifically focus on the findings pertaining to the largest urban area of the department, Medellín, along with its metropolis. We discuss how the current development agenda, centered around turning the city into a technological and business hub, intertwined with a bilingualism program, poses challenges to language education. In addition, we discuss how city development plans that have an effect on education are influenced by neoliberal discourses centered on ideas of economic development and competition.